Statistical Analysis of COVID cases in India. Issue 1 (February 2021) - Das, Subhranil; Kumari, Rashmi
Abstract: The novel coronavirus SARS-COV-2(COVID 19) has been considered as pandemic in the month of February as declared by World Health Organization. The cause of Coronavirus is due to group of RNA Viruses that mainly causes diseases in animals where this disease can be transferred to humans by droplets which ultimately results to death if it is not cured at early stages. But, in India, COVID cases has begun towards the end of February as the cases has been spiked in the month of March. In this paper, a complete analysis of Statistics for COVID cases has been demonstrated till the month of August. Using Statistical Measures, inferences are being drawn on the basis of COVID data on confirmed, recovered, active as well as death cases.